Design and Development of Flow Analyzer for Peak Inspiratory Flow (PIF) and Peak Expiratory Flow (PEF) Parameters. - Andri Lazuardi Wahyu Pambudi; Endro Yulianto; Levana Forra Wakidi (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
The PIF and PEF parameters on the ventilator need to be taken into account to monitor the condition of patients undergoing mechanical ventilation. Both of these parameters need to undergo periodic testing to ensure that the ventilator can provide accurate information to its users. The testing of these two parameters can be conducted using a flow analyzer. The objective of this research is to develop a flow analyzer for PIF and PEF parameters using the AFM3000 flow sensor, with the results displayed on an LCD TFT screen in the form of graphs and numerical values. The research measurements were conducted in Volume Control (VC) mode with VT settings of 200, 300, 400, 500, and 600 mL. Data collection was done using two methods to obtain two different types of data. From the first data collection, the largest errors in reading PIF and PEF values were found to be 3.49% and 2.99%, respectively. The second data collection resulted in a sensor's change in reading constant flow of ±0.1 LPM. Overall, the research findings indicate that the AFM3000 sensor has good accuracy and stability. Additionally, the AFM3000 flow sensor has good sensitivity and very short delay, making it suitable for real-time graph display in the module.